Monitoring Severity of Multiple Organ Dysfunction Syndrome: New Technologies. Issue 3 (March 2017) - Typpo, Katri V.; Wong, Hector R.; Finley, Stacey D.; Daniels, Rodney C.; Seely, Andrew J. E.; Lacroix, Jacques
Abstract : Objective: To describe new technologies (biomarkers and tests) used to assess and monitor the severity and progression of multiple organ dysfunction syndrome in children as discussed as part of the Eunice Kennedy Shriver National Institute of Child Health and Human Development MODS Workshop (March 26–27, 2015). Data Sources: Literature review, research data, and expert opinion. Study Selection: Not applicable. Data Extraction: Moderated by an experienced expert from the field, investigators developing and assessing new technologies to improve the care and understanding of critical illness presented their research and the relevant literature. Data Synthesis: Summary of presentations and discussion supported and supplemented by relevant literature. Conclusions: There are many innovative tools and techniques with the potential application for the assessment and monitoring of severity of multiple organ dysfunction syndrome. If the reliability and added value of these candidate technologies can be established, they hold promise to enhance the understanding, monitoring, and perhaps, treatment of multiple organ dysfunction syndrome in children.